Chelate-enhanced phytoextraction and phytostabilization of lead-contaminated soils by carrot (Daucus carota). Issue 3 (3rd March 2016) - Babaeian, Ebrahim; Homaee, Mehdi; Rahnemaie, Rasoul
Abstract : The objective of this study was to study the influence of different ethylenediamine tetraacetate (EDTA), nitrilotriacetic acid (NTA) and oxalic acid (HOx) concentrations on tolerance and lead (Pb) accumulation capacity of carrot ( Daucus carota ). The results indicated that by increasing Pb, NTA and HOx concentrations in the soil, the shoot, taproot and capillary root dry matters increase effectively. In contrary, EDTA caused to reduce capillary roots biomass. EDTA was more effective than NTA and HOx in solubilizing soil Pb. The highest Pb content in shoots (342.2 ± 13.9 mg kg −1 ) and taproots (301 ± 15.5 mg kg −1 ) occurred in 10 mM EDTA, while it occurred for capillary roots (1620 ± 24.6 mg kg −1 ) in 5 mM HOx, when the soil Pb concentration was 800 mg kg −1 . The obtained high phytoextraction and phytostabilization potentials were 1208 (±25.6) and 11.75 (±0.32) g Pb ha −1 yr −1 in 10 mmol EDTA kg −1 soil and no chelate treatments, respectively. It may be concluded that chelate application increases Pb uptake by carrots. Consequently, this plant can be introduced as a hyperaccumulator to phytoextract and phytostabilize Pb from contaminated soils.